Upaya Meningkatkan Kepercayaan Diri Siswa dalam Berbicara di Depan Umum dengan Media Modul dan Tugas Tantangan - Istikakimi; Venna Kurniawati (Jurnal Studi Pendidikan Dasar, 2024)
Low self-confidence in public speaking is one of the main barriers to developing communication skills in school environments. This study aims to examine the effectiveness of using modules and challenge tasks as strategies to enhance students’ self-confidence through a literature review approach. Based on preliminary data from students it was found that many students experience nervousness, lack of focus, and self-doubt when asked to speak in public. Drawing on Bandura’s theory of self-efficacy and relevant previous research, the study concludes that the proper use of media can help students overcome psychological barriers. The module serves as a systematic guide introducing basic communication concepts and cognitive exercises, while challenge tasks act as a practical medium that allows students to gradually build confidence through direct experience. The results indicate that this combination effectively fosters mastery experiences, strengthens students’ positive perceptions of their abilities, and creates a pattern of courage in public speaking.